COVID-19-Related Changes in NO2 and O3 Concentrations and Associated Health Effects in Malta - Fenech, Sara; Aquilina, Noel J.; Vella, Ryan (Frontiers in Sustainable Cities, 2021)
The start of 2020 has been characterized by emission reductions in various countries across the globe following the implementation of different lock-down measures to control the transmission of the SARS-CoV-2 (COVID-19). Consequently, these reductions influenced the air quality globally. In this study, we focus on daily nitrogen dioxide (NO2) as well as ozone (O3) concentrations measured across the Maltese Islands between January and mid-October 2020. Changes in air quality are generally difficult to detect due to the complex composition and interactions occurring within the atmosphere. To quantify changes in NO2 and O3 concentrations during the COVID-19 period, we use a random forest machine learning algorithm to determine a business as usual counterfactual scenario. Results highlight a decrease in monthly mean NO2 concentrations by up to 54% in the traffic site of Msida ( 21 μg m−3). In contrast, the monthly mean O3 concentrations during the COVID-19 months are up to 61% higher compared to a business as usual scenario in Msida ( 28 μg m−3). In this study, we also estimate the differences in attributable fraction (AF) associated with short-term exposure to NO2 and O3 concentrations. In Msida, the AF is up to 0.9% lower and 0.8% higher for measured NO2 and O3 concentrations, respectively. Our results highlight the favorable effects of decreasing traffic-related emissions on NO2 concentrations however, we also note increases in other pollutants for example O3 concentrations which especially in the short-term can lead to various adverse health effects.